When Coproduction Is Unproductive; Comment on "Experience of Health Leadership in Partnering with University-Based Researchers in Canada: A Call to 'Re-Imagine' Research" - Sara A. Kreindler (Kerman University of Medical Sciences, 2020)
Bowen et al offer a sobering look at the reality of research partnerships from the decision-maker perspective. Health leaders who had actively engaged in such partnerships continued to describe research as irrelevant and unhelpful - just the problem that partnered research was intended to solve. This commentary further examines the many barriers that impede researchers from meeting decision-makers' knowledge needs, and decision-makers from using knowledge that they have coproduced. It argues that not all barriers can or should be dismantled: some are legitimate and beneficial; some are harmful but deeply entrenched; some arise unpredictably. This being the case, it seems unrealistic to expect either existing or emerging strategies to create a macro-context devoid of barriers to the fruitful coproduction of knowledge. However, it may be possible to identify and support micro-contexts (configurations of participants, settings, and project characteristics) in which partnered research is most likely to achieve its aims.